PENGARUH PENGETAHUAN INVESTASI, MODAL AWAL INVESTASI, DAN KEMAJUAN TEKNOLOGI TERHADAP MINAT INVESTASI MAHASISWA - Putri, Nelly Prima; Andriani, Irma (Ensiklopedia of Journal, 2025)
This study aims to evaluate the effect of investment knowledge, initial investment capital, and technological progress on students' investment interest. The study was conducted using a quantitative approach. The population in this study were active students of Universitas Putra Indonesia YPTK Padang. The sampling technique was purposive sampling. The number of samples used was 100 people. The data analysis used was Smart PLS software version 4.0. The results of this study indicate that investment knowledge, initial investment capital and technological progress have an effect on students' investment interest.Keywords: Investment knowledge, initial investment capital, technological progress, investment interest.